Smoking in social housing among adults in England, 2015–2020: a nationally representative survey. Issue 7 (26th July 2022) - Jackson, Sarah E; Cheeseman, Hazel; Arnott, Deborah; Titmarsh, Robbie; Brown, Jamie
Abstract : Objectives: To analyse associations between living in social housing and smoking in England and to evaluate progress towards reducing disparities in smoking prevalence among residents of social housing compared with other housing types. Design: Cross-sectional analysis of nationally representative data collected between January 2015 and February 2020. Setting: England. Participants: 105 562 adults (≥16 years). Primary and secondary outcome measures: Linear and logistic regression were used to analyse associations between living in social housing (vs other housing types) and smoking status, cigarettes per day, time to first cigarette, exposure to others' smoking, motivation to stop smoking, quit attempts and use of cessation support. Analyses were adjusted for sex, age, social grade, region and year. Results: Adults living in social housing had two times the odds of being a smoker (ORadj =2.17, 95% CI 2.08 to 2.27), and the decline in smoking prevalence between 2015 and 2020 was less pronounced in this high-risk group (−7%; ORadj =0.98, 95% CI 0.96 to 1.01) than among adults living in other housing types (−24%; ORadj =0.95, 95% CI 0.94 to 0.96; housing tenure–survey year interaction p=0.020). Smokers living in social housing were more addicted than those in other housing types (smoking within 30 min of waking: ORadj =1.50, 95% CI 1.39 to 1.61), but were no less motivated to stop smoking (ORadj =1.06, 95% CI 0.96 to 1.17) and had higher odds of having made a serious attempt to quit in the past year (ORadj =1.16, 95% CI 1.07 to 1.25). Among smokers who had tried to quit, those living in social housing had higher odds of using evidence-based cessation support (ORadj =1.22, 95% CI 1.07 to 1.39) but lower odds of remaining abstinent (ORadj =0.63, 95% CI 0.52 to 0.76). Conclusions: There remain stark inequalities in smoking and quitting behaviour by housing tenure in England, with declines in prevalence stalling between 2015 and 2020 despite progress in the rest of the population. In the absence of targeted interventions to boost quitting among social housing residents, inequalities in health are likely to worsen.